Pengaruh Ekstrakurikuler Robotik terhadap Prestasi Belajar Siswa di MIN 2 Kabupaten Kediri - Miftahuddin; Nuraida, Dilla (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This research aims to determine whether there is an effect of robotic extracurriculars on the learning achievement of students participating in Robotics Extracurriculars at MIN 2 Kediri Regency and to determine how big the level of influence is. This research was conducted using a quantitative approach, the sample in this study used a sample of 20 people consisting of students in grades 3-5 who took part in Robotics Extracurriculars at MIN 2, Kediri Regency. This research uses two kinds of variables, namely: 1) independent variable: Robotics Extracurricular (X), 2) Dependent Variable: Learning Achievement (Y). Data collection for Robotic Extracurricular variables and Learning Achievement used a questionnaire method with a Likert scale. The validity of the data is obtained through validity and reliability tests. The data analysis technique used is descriptive analysis to calculate the mean, median, mode, and standard deviation. Data analysis for hypothesis testing used normality test and simple linear regression analysis and to find out the percentage of the degree of influence of variable X on variable Y used the coefficient of determination using SPSS for Windows version 29 software. There was a positive effect of robotic extracurricular activities on the learning achievement of students participating in extracurriculars Robotics at MIN 2 Kediri Regency is proven by data analysis it is known that the calculated F value is 8,960 with a significance level of 0.008 ˂ 0.05, then the model can be used thus Ho is rejected and Ha is accepted meaning to predict Robotics Extracurricular variables or in other words there is the effect of the Robotic Extracurricular variable (X) on the Learning Achievement variable (Y). From the data obtained the coefficient of determination (R Square) is 0.332, which means that the effect of the independent variable (Robotic Extracurricular) on the dependent variable (Learning Achievement) is 33.2%.